Work engagement among millennial employees: The role of psychological capital and perceived organizational support - Gumilang, Nabila Ayu; Indrayanti, Indrayanti (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
Millennials, who have several values, perspectives, and habits different from previous generations, have dominated the profile of workers in Indonesia. Challenges and changes in the company require millennials to be engaged in their work. This study aimed to determine the work engagement of millennial employees through the role of psychological capital and perceived organizational support. The research participants were 225 millennial employees with a minimum working period of six months. The work engagement scale (UWES-17), Psychological Capital Questionnaire (PCQ), and Perceived Organizational Support Scale were used to collect the data. This research was conducted using quantitative methods and analyzed by multiple regression analysis. The results show that psychological capital and perceived organizational support simultaneously contribute to work engagement among millennial employees. Independently, psychological capital and perceived organizational support significantly predict work engagement. These findings indicate both personal factors and situational factors are needed to achieve work engagement. Thus, the finding represents the existence of positive psychological movement on work engagement through the lens of the psychological process mechanism at work.